Mycobacterium kansasii osteomyelitis – a masquerading disease. (2nd January 2018) - Bhatt, Kiranmai; Banavathi, Krishna
Abstract : Introduction. Non-tuberculous mycobacteria (NTM) are environmental bacteria capable of causing an opportunistic myriad of infections. Mycobacterium kansasii, one such NTM, is responsible for causing pulmonary disease in immunocompromised patients. Rare extrapulmonary manifestations such as lymphadenitis, osteoarticular manifestations, and skin and soft tissue infections are also observed. Case presentation. Here, we report an unusual case of sternoclavicular joint and elbow joint infection with M. kansasii in a relatively immunocompetent patient. Histopathology did not show classic granulomas and mycobacterial infection was not initially considered as a possibility. However repeat biopsies were sent for mycobacterial cultures which then grew M. kansasii . Conclusion. Diagnosis of M. kansasii in such cases can be difficult and culture-positive results may not necessarily imply positive diagnosis as they can be environmental contaminants. Furthermore, M. kansasii can cause infections without the characteristic granuloma formation, which can further complicate tissue diagnosis. This underlines the importance of ensuring that tissue samples obtained are cultured for mycobacteria.